Students’ Acceptance through the Using of Project Based Learning Model in Learning RELT Subject - Arini; Harida, Eka Sustri; Siregar, Sri Rahmadhani (ELITE Association Indonesia, 2023)
ABSTRACT Project based learning is a method that focusing on students centered by using project as the way of practicing knowledge. RELT subject is a subject learnt about research in English framework. This research aim is to know students’ acceptance of using project based learning in learning RELT subject. The researched also gain the feedback after using this method. This research using quantitative method by (Creswell 2014). Technique sampling was purposive sampling. The sample were sixty students from sixth semester. Instrument of the research was questionnaire. The data analysis using Likert scale. Using Project based learning in different level of students also give the difference result. Using PjBL in learning RELT subject was effective. It can be shown from the data result, the mean score was 76% students agree with the using of project based learning metjod in learning RELT subject. The data shown each statements answer was only 2-3 students who answered disagre. Students felt comfortable. Here researcher can know that the using of projects based learning accepted. Keywords: Students, Respond, PjBL Method, RELT Subject, English Student